2015
DOI: 10.1155/2015/730640
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bending Process Parameters for Seamless Tubes Using Taguchi Method and Finite Element Method

Abstract: The three-dimensional tube (or pipe) is manufactured by CNC tube bending machine. The key techniques are determined by tube diameter, wall thickness, material, and bending radius. The obtained technique through experience and the trial and error method is unreliable. Finite element method (FEM) simulation for the tube bending process before production can avoid wasting manpower and raw materials. The computer-aided engineering (CAE) software ABAQUS 6.12 is applied to simulate bending characteristics and to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The obtained results show that the strain measurement by using two different methods, namely the Taguchi method and Computer Aided Engineering (CAE) software ABAQUS 6.12, has a margin error of 6.39%. This highlights the reliability and robustness of the Taguchi method [15].…”
Section: Taguchimentioning
confidence: 78%
See 2 more Smart Citations
“…The obtained results show that the strain measurement by using two different methods, namely the Taguchi method and Computer Aided Engineering (CAE) software ABAQUS 6.12, has a margin error of 6.39%. This highlights the reliability and robustness of the Taguchi method [15].…”
Section: Taguchimentioning
confidence: 78%
“…By using the trial and error method, it has been shown that the collected data is unreliable. Hence the use of the Taguchi method improves the reliability of the data collection [15]. The obtained results show that the strain measurement by using two different methods, namely the Taguchi method and Computer Aided Engineering (CAE) software ABAQUS 6.12, has a margin error of 6.39%.…”
Section: Taguchimentioning
confidence: 95%
See 1 more Smart Citation
“…This method employs a statistical measurement named as the ratio of the mean (called signal) to the standard deviation (called noise) (S/N), which represents a logarithmic function of wanted output. There are three standard types of S/N ratio; higher the better (HB), lower the better (LB) and Nominal the best (NB) [22] and [23]. In this study, the higher critical load of buckling is required, therefore, the higher the better formula is used:…”
Section: Taguchimentioning
confidence: 99%
“…It can be used to obtain the relationship between the observed manufacturing process and its products [5,35]. The major advantage of the Taguchi method is the ability to analyze the observed process with a small number of experiments.…”
Section: Design Of Experimentsmentioning
confidence: 99%